Can FinTech shape the dynamics of consumer credit usage among the un(der)banked? - Davis Bundi Ntwiga (Kenya Bankers Association (KBA), 2019)
We use the 2016 FinAccess Household survey data of 2015 from 8665 households and desktop reviews to examine how perceptions, behaviour, financial literacy and socioeconomic characteristics of un(der) banked consumers can shape their dynamics towards credit usage. The challenges and opportunities for the market players are examined using desktop reviews and their role towards an increase in financial inclusion and credit usage through FinTech. The disruptive innovations have provided new possibilities, challenges and opportunities to boost financial and credit usage in the market. Consumer perceptions on cost, trust, source of financial advice, financial literacy and socio-economic characteristics influences credit usage. The business models being developed by the FinTech providers are taunted to change the landscape of lending to the un(der) banked.
Keywords: G00; G41; G23; 330; FinTech; un(der)banked; credit usage; perceptions and behaviour; challenges; opportunities; socio-economic characteristics